Peran Mediasi Adiksi Media Sosial dalam Pengaruh FOMO terhadap Kecemasan Sosial pada Dewasa Awal - Vanessa Clarence; Agoes Dariyo (Lembaga Yasin AlSys, 2026)
The development of digital technology has made social media an integral part of Generation Z’s daily life; however, the intensity of its use is also associated with increasing mental health problems, one of which is social anxiety. Fear of Missing Out (FoMO) is a psychological factor that drives individuals to remain constantly connected via social media and has the potential to trigger addictive use. This study aimed to examine the role of social media addiction in the effect of FoMO on social anxiety among early adults in the Greater Jakarta (Jabodetabek) area. A non-experimental quantitative approach with an explanatory design was employed, involving 380 participants aged 18–25 years who were active social media users and selected through purposive sampling. The instruments used included the Social Anxiety Scale for Social Media Users (SAS-SMU), the Bergen Social Media Addiction Scale (BSMAS), and a FoMO scale, all of which had undergone adaptation, validity testing, and reliability testing. Data were analyzed using correlation tests and mediation analysis with PROCESS model 4. The results showed that FoMO had a positive and significant relationship with social anxiety (r = 0.692; p < 0.001) and a positive effect on social anxiety (β = 0.642), as well as a positive and significant relationship with social media addiction (r = 0.788; p < 0.001) with a positive effect (β = 0.483). Social media addiction also had a positive and significant relationship with social anxiety (r = 0.696; p < 0.001) and a positive effect (β = 1.105). The effect of FoMO on social anxiety mediated by social media addiction showed an indirect effect of β = 0.534, indicating partial mediation. Thus, FoMO contributes to increased social anxiety both directly and indirectly through social media addiction among early adults. These findings underscore the importance of managing social media use and implementing preventive interventions to minimize negative psychological impacts on Generation Z.